2016
DOI: 10.1111/jep.12551
|View full text |Cite
|
Sign up to set email alerts
|

At‐home monitoring after surgery/anaesthesia – a challenge

Abstract: Bringing telemedicine into follow-up after surgery/anaesthesia is requested, and furthermore, the feasibility study on day surgery presented here shows that it is technically easy to perform and will provide robust information. It should be noted that further studies are needed in order to find better patient cooperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…19 The remaining 2 apps were in Swedish. 32,37 All apps had features to assess the patient postoperatively and 1 app included preoperative information and reminders as well as postoperative monitoring features. 38 Nine of the 11 articles had an app that allowed submission of a digital photo of the surgical wound.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The remaining 2 apps were in Swedish. 32,37 All apps had features to assess the patient postoperatively and 1 app included preoperative information and reminders as well as postoperative monitoring features. 38 Nine of the 11 articles had an app that allowed submission of a digital photo of the surgical wound.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the results of Warren-Stomberg et al 37 indicated that patients older than 60 years would prefer paper-based follow-up methods, this may not be the case in the coming years, as 79% of 65- to 75-year-olds had access to a smartphone in Sweden. 42 Additionally, there has been an increase in the use of smartphones from 29% in 2012 to 71% in 2017 for people aged between 55 and 75 years in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a telephone call is made 1 day after the surgery (Stomberg et al, 2013; Segerdahl et al, 2008). There is a growing body of research on the use of digital follow-up tools (Semple et al, 2015; Armstrong et al, 2017; Warren-Stomberg et al, 2016; Nilsson et al, 2016; Williams et al, 2018), including digital tools that patients find easy to use (Semple et al, 2015; Dahlberg et al, 2016; Jaensson et al, 2015; Debono et al, 2016) and that have a positive effect on postoperative recovery (Jaensson et al, 2017). Digital follow-up has been described by patients as increasing their feeling of safety and helping them to not feel alone after day surgery (Dahlberg et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Des robots ont même été mis au point et testés à la fois sur mannequin et sur humains pour les gestes techniques de type intubation et anesthésie loco-régionale [22] . De même, des équipes s’intéressent au suivi postopératoire en télémédecine, que ce soit en chirurgie ambulatoire via des applications pour smartphones ou en hospitalisation en soins critiques [23] , [24] . Aussi, la télémédecine pourrait à terme connaître un essor majeur dans la gestion anesthésique périopératoire des patients et pourrait bien bouleverser rapidement bousculer nos pratiques actuelles.…”
Section: Discussionunclassified